Estrategias didácticas para el desarrollo de la capacidades físicas en las clases de educación física en los estudiantes de noveno año de la Unidad Educativa Isabel La Católica. - Mendoza Sánchez, Josélyn Martha (2025)
This project entitled didactic strategies for the development of physical abilities in physical education classes in ninth year students of the isabel la católica educational unit" aims to investigate and propose didactic strategies that facilitate the development of physical abilities in students. Through a mixed approach, it explored how current pedagogical practices influence the improvement of young people's physical health and well-being. The research focused on identifying effective methods that teachers can implement to encourage healthy habits, addressing the need for comprehensive physical education that not only focuses on competence, but also on disease prevention and the promotion of an active lifestyle.